Acute symptomatic seizures and ventricular fibrillation - a multimodality approach to a rare complication of myocardial infarction. Case report - Miruna Florina Stefan; Stefania Lucia Magda (Sciendo, 2021)
Background - 6-8% of patients with acute myocardial infarction still develop ventricular arrhythmias (VA), although their incidence has lowered due to prompt antiischemic treatment. VA might determine sometimes acute symptomatic seizures. Case report - A 44-year old male was admitted to our unit with acute inferior myocardial infarction. Emergency coronary angiography was performed and revealed acute occlusion of the right coronary artery. The procedure was complicated by coronary dissection, which was sealed, with good final results. After admission in the acute coronary unit, the patient developed ventricular fibrillation. He was successfully resuscitated, but developed ongoing tonic-clonic seizures, terminated after intravenous administration of several anticonvulsivant drugs. We investigated the patient for epilepsy and for other pathologies that could explain both the VA and the seizures. All investigations were within normal range. Conclusion - Differential diagnosis between hypoxic and epileptic seizures is difficult and important, because it further influences patient management. Cardiac arrhythmias are a rare precipitating factor for acute symptomatic seizures, due to hypotension-induced cerebral hypoxemia. Our case illustrates the value of a multimodal approach of rare complication of a myocardial infarction.